1989
DOI: 10.2166/wst.1989.0240
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Flow Patterns in Enhanced Biological Phosphorus Accumulating Activated Sludge Cultures

Abstract: Intracellular carbon flow in enhanced biological phosphorus accumulating cultures was tracked by using radiolabelled glucose and acetate as substrates. Batch studies using the labelled substrates verified that acetate and glucose were metabolized differently and acetate would be a more effective source of organic material for carbon supplementation. The use of acetate ensures that the greatest percentage of added carbon will be sequestered by phosphorus accumulating species. Carbon flow was also evaluated in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Originally it was thought that the citric acid cycle provides the reducing equivalents for the conversion of acetyl-CoA into PHB. However, the almost complete lack of 1 4 C0 2 formation from 14C-labeled acetate (Bordacs and Chiesa, 1989) and the significant decrease in cellular glycogen during the nonaerated period (Mino et aI., 1987) point to a production of reducing equivalents by glycolysis. The acetyl-CoA formed during glycolysis is thought to be converted into PHB.…”
Section: A Biochemical Modelmentioning
confidence: 99%
“…Originally it was thought that the citric acid cycle provides the reducing equivalents for the conversion of acetyl-CoA into PHB. However, the almost complete lack of 1 4 C0 2 formation from 14C-labeled acetate (Bordacs and Chiesa, 1989) and the significant decrease in cellular glycogen during the nonaerated period (Mino et aI., 1987) point to a production of reducing equivalents by glycolysis. The acetyl-CoA formed during glycolysis is thought to be converted into PHB.…”
Section: A Biochemical Modelmentioning
confidence: 99%
“…These findings indicate that the composition of PHA could be a useful parameter for the identification of the relevant metabolic pathways. Radioactively labeled acetate as the carbon source for the EBPR process was also used for the same purpose (Bordacs and Chiesa, 1989;Pereira et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The pH profile showed a mirror image to the CO2 and decreased (less than 0.01/minute in rate) after the addition; this implied that the pH change was due to the biological reaction. A 14 C tracing study suggested that the CO2 monitoring was not practical in a biological phosphorus release reaction, because of insignificant CO2 changes (Bordacs and Chiesa, 1989). However, in comparison with pH-buffered tests in this study, it was confirmed that the pH change in the reaction helped to result in distinguishing overall CO2 change.…”
Section: Batch Testsmentioning
confidence: 54%